Distribution updates of the yellow-bellied weasel Mustela kathiah in the Kathmandu Valley, Nepal - Gosai, Kamal Raj; Beejukchhen, Dasrath Shrestha; Khatri, Shree Ram; Shrestha, Tej Kumar; Katuwal, Hem Bahadur (Nepalese Journal of Zoology, 2022)
Yellow-bellied weasel (Mustela kathiah) is one of the least known small carnivores of Nepal. Although it is assumed to distribute within the mid-hills region, its sightings are very few in Nepal. We updated its distribution from Kathmandu Valley based on literature review and opportunistic sightings. Now, the yellow-bellied weasel is known from three locations in the Kathmandu Valley (Phulchowki, Budhanilkantha, and Dallu-Pharping) between 1300 and 2710 meters above sea level (m asl). Only one individual was sighted in each observation. The observation from Phulchowki (2710 m asl) represents the highest elevation record for the Kathmandu Valley and the second highest for Nepal. The weasels were observed in the forest, bushes, and agricultural areas near small rivers and human settlements.